The dual function of soil: natural resources and production site - Várallyay, György; Láng, István (Acta Agraria Debreceniensis, 2001)
First, we begin with a review of the global situation, followed by a description of that in Hungary itself. Next, we consider the conditions affecting soil utilization, and their relevant problems. Finally, we make a brief prediction of what can be expected in the coming two decades or so. For this latter reason, it is necessary to briefly illustrate the situation, processes and relationships.